2010
DOI: 10.1007/s12298-010-0015-9
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of genetic diversity through RAPD, ISSR and AFLP markers in Podophyllum hexandrum: a medicinal herb from the Northwestern Himalayan region

Abstract: Total synthesis of podophyllotoxin is an expensive process and availability of the compound from the natural resources is an important issue for pharmaceutical companies that manufacture anticancer drugs. In order to facilitate reasoned scientific decisions on its management and conservation for selective breeding programme, genetic analysis of 28 populations was done with 19 random primers, 11 ISSR primers and 13 AFLP primer pairs. A total of 92.37 %, 83.82 % and 84.40 % genetic polymorphism among the populat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
22
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(30 citation statements)
references
References 28 publications
8
22
0
Order By: Relevance
“…Furthermore, the Mantel test revealed that the genetic distance between populations did not correlate with the geographical distance. Restricted gene flow associated with geographical distance is consistent with the results of previous studies on this species (Alam et al, 2008;Alam et al, 2009;Naik et al, 2010).…”
Section: High Genetic Differentiation and Distinct Genetic Structuresupporting
confidence: 91%
See 3 more Smart Citations
“…Furthermore, the Mantel test revealed that the genetic distance between populations did not correlate with the geographical distance. Restricted gene flow associated with geographical distance is consistent with the results of previous studies on this species (Alam et al, 2008;Alam et al, 2009;Naik et al, 2010).…”
Section: High Genetic Differentiation and Distinct Genetic Structuresupporting
confidence: 91%
“…Comparing the average genetic diversity with that of S. hexandrum from other regions (Xiao et al, 2006b;Alam et al, 2008;Naik et al, 2010;Liu et al, 2014) and with other Berberidaceae species (Qiu et al, 2006;Zong et al, 2008) based on the ISSR approach showed that S. hexandrum populations have low genetic diversity (average H E = 0.0366). The S. hexandrum populations from the Northwestern Himalayan region (Xiao et al, 2006b;Alam et al, 2008;Naik et al, 2010) (average H E = 0.2944, 0.092, respectively) and Qinling Mountains (average H E = 0.0621) showed high genetic diversity. S. hexandrum is native to the Himalayan region, where it grows in valleys with secondary vegetation, under shrubs, or around trees (Ma and Hu, 1996).…”
Section: Genetic Diversity Of S Hexandrummentioning
confidence: 97%
See 2 more Smart Citations
“…It is also used in the investigation of genetic diversity within and among populations thus provides valid evidence for genetic relatedness (Crawford, The DNA molecular markers are not influenced by the external environmental factors unlike that of morphological and biochemical markers, which had its own limitations as they were always, do not completely represent the genetic structure (Noli et al, 1997) and hence accurately testify the genetic relationship between and among individual groups (Lawrence et al, 1992). Inter-simple sequence repeats (ISSR)has been used regularly for genetic diversity assessment as a thorough knowledge of the level and distribution of genetic variation (of length of DNA fragments between simple sequence repeats), which was essential for conservation (Dreisigacker et al, 2005;Sharma et al, 2008;Naik et al, 2010 andDas et al, 2011). This PCR-based DNA finger printing technique was proven to be very informative and costeffective technique in many individual species as their primers do not require prior knowledge of a species genome (Williams et al, 1990;Zietkiewicz et al, 1994;Kharazian et al, 2015 andBadr et al, 2014;.…”
Section: Introductionmentioning
confidence: 99%